Proboscis lateralis - Agarwal, Salil (Springer-Verlag, 2010)
Proboscis lateralis is a rare craniofacial malformation for which no embryological basis has been established. The condition presents with a tubular, nose like structure arising from the medial canthal area or orbit roof. We describe here such a case that was surgically treated.